TRANSFORMATION OF HEALTH TERMINOLOGY THROUGH DERIVATIONAL AFFIXATION IN CNN ONLINE NEWS - Wulandari, Sari; Yatmikasari, Ika; Sariyati, Ice (CALL, 2023)
Derivational affixation is a linguistic process that involves the creation of new words by adding prefixes, suffixes, or infixes to existing words. These affixes can modify the word's part of speech, alter its meaning, or both. The present study had the objective of identifying various types of derivational affixes and examining the morphological transformations they bring about in health-related terms within CNN's online news platform. Employing qualitative research methods informed by Katamba's theoretical framework (2005), the investigation utilized a dataset sourced from the news website https://edition.cnn.com/. The dataset encompassed 30 health-related news articles spanning topics such as COVID-19, mental health, food, beauty, sleep, and pregnancy. Based on data analysis from 30 health news, there were 13 words containing derivational prefixes and 64 words containing derivational suffixes. The words in derivational prefix did not change the part of speech but changed the meaning. In derivational suffixes, there are 7 types of changes that change word from verb to noun (23 words), adjective to noun (14 words), noun to noun (10 words), noun to adjective (7 words), adjective to adverb (5 words), verb to adjective (4 words), and the last noun to verb (1 word). From the findings, it can be concluded that the addition of affixes to words explains the function of sentence structure. Derivational suffixes are found the most because they have many interactions of forms, meanings, and functions.Â Keywords: derivational affix, health, prefix, suffix, news